Symbolic Efficacy in the Psychiatric Ward: A Clinical Ethnography of Cetik-Attributed Psychosis and Hospital-Facilitated Ritual Integration in Bali - Ni Wayan Saka Rahayu; Ni Made Citra Riesti Wulan; Nyoman Ari Yoga Wirawan; Ida Bagus Ngurah Dwipayana Manuaba (Enigma Institute, 2025)
In Bali, acute psychosis is frequently interpreted through the Niskala or unseen cosmology, specifically attributed to Cetik or magical poisoning and Guna-guna or sorcery. This explanatory model often clashes with biomedical paradigms, leading to poor therapeutic alliance and treatment refusal. This study aims to evaluate the pathoplastic efficacy and symbolic healing mechanisms of an integrative therapeutic approach. We employed a clinical ethnography design within a psychiatric ward in Denpasar, Bali. The subject was a 26-year-old Balinese female with Acute and Transient Psychotic Disorder (ICD-10: F23.2), presenting with severe psychomotor agitation (PANSS-EC score of 22). Data were collected via the DSM-5 Cultural Formulation Interview (CFI), non-participant observation of a hospital-facilitated Penglukatan or purification ritual, and clinical timeline mapping. We utilized a rigorous reflexivity framework to analyze the intersection of the clinical gaze of the psychiatrist and the ritual authority of the Balian or traditional healer. The distress of the patient was culturally coded as